Determination of strain rate in Friction Stir Welding by three-dimensional visualization of material flow using X-ray radiography. (September 2015) - Morisada, Y.; Imaizumi, T.; Fujii, H.
Graphical abstract: Abstract : Recrystallization, which is mainly caused by the induced strain, is one of the most important factors of Friction Stir Welding. In this study, strain and strain rate are directly obtained by the change in the material flow velocity which is observed by three-dimensional visualization of the material flow. The grain size of the pure aluminum in the stir zone estimated by the Zener–Hollomon parameter using the obtained strain rate shows good agreement with that observed by Electron Back-Scatter Diffraction mapping.